2022
DOI: 10.1186/s12905-022-01773-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sleep quality, neck pain, shoulder pain and disability, physical activity, and health perception among middle-aged women: a cross-sectional study

Abstract: Background Sleep quality is an important physical requirement for a healthy life, and good sleep quality has been recognized as a significant component in physical and mental health and well-being. The purpose of this study was to identify the factors that affect sleep quality as well as the relationship between sleep quality and neck pain, shoulder pain and disability, physical activity, and health perception. Methods We conducted surveys on 494 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Furthermore, in previous studies, it was found that the quality of sleep tended to be poorer in subjects with multiple illnesses compared to those with a single disease. [ 47 , 48 ] Our study also identified a considerable proportion of patients diagnosed with comorbidities in addition to cardiovascular disease. Since we did not investigate whether the medication these patients were taking had an impact on their quality of sleep or fatigue, we propose the need for further research as a follow-up study.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, in previous studies, it was found that the quality of sleep tended to be poorer in subjects with multiple illnesses compared to those with a single disease. [ 47 , 48 ] Our study also identified a considerable proportion of patients diagnosed with comorbidities in addition to cardiovascular disease. Since we did not investigate whether the medication these patients were taking had an impact on their quality of sleep or fatigue, we propose the need for further research as a follow-up study.…”
Section: Discussionmentioning
confidence: 79%
“…[34] From the perspective of social factors, compared with men, women may have more types of social burdens, such as housework burden, childcare burden, work burden, and children’s education burden, which will lead to poor sleep quality of women. [35,36] From the perspective of physiological factors, with the arrival of menopause, the estrogen level and physiological function of women gradually decline, [37] and the sleep quality of women may be affected by significant changes in hormones. [38] Psychological factors are also important factors that affect sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the association between routinary physical activity and disability, Lee et al [ 52 ] analyzed the association between the IPAQ and neck disability (assessed with the Northwick Park Neck Pain Questionnaire) and found no significant associations. Since they did not differentiate physical activity type, this may explain the results’ differences with our study.…”
Section: Discussionmentioning
confidence: 99%